2002
DOI: 10.1139/g01-137
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of orthologous and paralogous DNA flanking the wheat high molecular weight glutenin genes: sequence conservation and divergence, transposon distribution, and matrix-attachment regions

Abstract: Extended flanking DNA sequences were characterized for five members of the wheat high molecular weight (HMW) glutenin gene family to understand more of the structure, control, and evolution of these genes. Analysis revealed more sequence conservation among orthologous regions than between paralogous regions, with differences mainly owing to transposition events involving putative retrotransposons and several miniature inverted transposable elements (MITEs). Both gyspy-like long terminal repeat (LTR) and non-LT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 43 publications
4
25
0
1
Order By: Relevance
“…MITE, miniature inverted-repeat transposable element. insertions are a major mechanism of divergence of paralogous and orthologous intergenic regions (Anderson et al, 2002). This notion is demonstrated here on a much larger scale.…”
Section: Mechanisms Of Genome Divergence At the Glu-a3/sfr159 Loci Insupporting
confidence: 57%
“…MITE, miniature inverted-repeat transposable element. insertions are a major mechanism of divergence of paralogous and orthologous intergenic regions (Anderson et al, 2002). This notion is demonstrated here on a much larger scale.…”
Section: Mechanisms Of Genome Divergence At the Glu-a3/sfr159 Loci Insupporting
confidence: 57%
“…Interspecific, intergeneric, and intertribal hybridization are a reality in the grasses. Although hybridization has long been postulated as a major source of variation in the grasses (Stebbins 1950), few wide crosses have been identified outside of experimental studies, and fewer yet (mostly in the wheat tribe, Triticeae) have been investigated in detail using sophisticated genetic analyses (Mason-Gamer 2001;Anderson 2002;Kishii 2002;Li 2002). Stabilized reticulation events of the distant past are difficult and time consuming to identify and characterize.…”
mentioning
confidence: 99%
“…There is no indication from this data that one duplication type was more conserved. Previous investigations have shown the orthologs are more highly conserved than the paralogs (Allaby et al 1999;Anderson et al 2002). Correlations between all combinations of glutenins and the control genes suggest chromosome group B has a common regulatory effect on glutenin paralogs and orthologs but not the control; group D had a common effect on Glu-B1-1:Glu-B1-2 and Glu-D1-2:Agp-L.…”
Section: Discussionmentioning
confidence: 81%
“…After gene duplication events, wheat has retained the functionality of some genes and silenced others. Anderson et al (2002) identified transposable element and retrotransposon sequences in the flanking regions of HMW glutenins and suggest these were a mechanism of sequence divergence after the initial duplication event. The HMW glutenin and Agp-L genes have revealed shared regulation of duplicated and tissuespecific genes: hypothetically, cis regulatory elements of the glutenin paralogs, orthologs and Agp-L share the recognition of trans regulators on several chromosome arms ( Fig.…”
Section: Agp-lmentioning
confidence: 95%
See 1 more Smart Citation